Determinants of innovative development on the example of Kazakhstan. Issue 4 (4th February 2021) - Nabieva, Maral; Turmakhanbetova, Shaken; Shamisheva, Nurgul; Khassenova, Kenzhegul; Baigabulova, Kulyash; Rakayeva, Aliya
Abstract : Purpose: Although many studies explored the drivers of innovative development and the innovation performance of different countries, very few studies looked at the association of the country's GII score with the qualitative indicators of innovation performance. The purpose of this paper is to contribute such an investigation by looking at the Republic of Kazakhstan (79th in 2019 GII ranking). Design/methodology/approach: This study looks at eight dynamic variables, among which one dependent (the GII score) and seven independent (R&D spending, innovation grants, the total cost of innovative goods and services, the percentage of innovative organizations, the share of innovative goods and services in gross domestic product (GDP) and the number of R&D staff and R&D institutions) variables associated with innovation performance. Changes in variables were tracked over the period from 2010 to 2018.. Findings: The study found that the Kazakhstan's GII score was reliant on variables, such as the percentage of innovative organizations, the value of innovative goods and services as a share of GDP, R&D spending and the cost of innovative goods and services. At the same time, the number of R&D institutions, innovation grants and number of R&D staff had no substantial impact on the GII score of Kazakhstan. Originality/value: Using the proposed approach, this study proved that factors, which have no direct association with the country's level of innovative development expressed in GII, could have a significant synergistic impact on this indicator.